URGENSI ADMINISTRASI PENDIDIKAN DALAM PENGELOLAAN MENINGKATKAN KUALITAS PENDIDIKAN DI MIS ISTIQOMAH SEI MENCIRIM - Mursal Aziz; Anggun Dela Pupita; Annisa Balqis; Windi Putri Arisqa (CV. Denasya Smart Publisher, 2024)
Our goal in this research is to find out how administration ismanagedat Madrasah Ibtidaiyah Istiqomah Sei Mencirim, howtoimprove the quality of madrasas. This research uses qualitative. The data collection technique that we use is observation, documentation and interviews. The results obtained are that the administrativemanagementatMadrasah Ibtidaiyah Istiqomah Sei Mencirimisgoingwell in improvingthequalityofmadrasas. The administration of the Madrasah curriculum has been going well, as evidenced by the students who successfully pass one hundred percent every year and Accreditation A. The quality can be seen from the curriculum, educators, and education staff. This research has a relationship between supervisors and Madrasah involvement. To study administrativemanagementat Madrasah Ibtidaiyah Istiqomah Sei Mencirim in improvingthequalityofMadrasas.